The collected works (gsuṅ ʼbum) of Glo-bo Mkhan-chen Bsod-nams-lhun-grub - Bsod-nams-lhun-grub, Glo Mkhan-chen (Ngawang Topgay, 1977)
Writings on Buddhism, both exoteric and esoteric, of a Sakyapa savant from Mustang in northern Nepal.